Stunting Analysis In Toddlers In West Java 2014-2021 - Ivanda Putra, Ersan; Sutomo, Rudi (Publisher Cv. Inara, 2023)
Stunting in toddlers is a global health problem affecting children's physical andmental development. This study aims to analyze the prevalence, trends, causes, and impact of stunting on toddlers in West Java province from 2014-2021. It also provides poor nutrition, sanitation, and access and healthcare practices. The analysis results show that although preventive and intervention efforts have been undertaken by the government, stunting rates in children under 5 years of age in West Java still remain high during the study period. Bad nutrition, especially bad nutrition in the first 1,000 days of life, was identified as the main cause of stunting in this region. In addition, poor hygiene and lack of access to health care also played a big role in this problem. Stunting has a serious impact on the physical and cognitive development of toddlers and can affect their productivity and health in the future. Therefore, real steps need to be taken to improve good nutritional access, provide education on the importance of nutrition in pregnancy and childhood, as well as improving the health infrastructure and medical services facilities in West Java. This study provides an in-depth understanding of stunting dynamics in children under 5 years of age at the regional level, so that it can serve as a foundation for more effective intervention policies and programs to lower the malnutrition rate.